THE EFFECT OF IMPLEMENTATION E-VOTING METHOD AS POLITICAL PARTICIPATION MEDIA ON EELECTION CHAIRMAN FOR CIVIC IMPROVMENT ON OSIS SENIOR HIGH SCHOOL 1 MANONJAYA OF CIVIC RESPONSIBILITY - Sunatra, Fajar Nugraha, Cecep Darmawan, (Department of Civic Education, 2014)
Indonesia is a country that upholds democracy. In fact the level of participations voters in every single show declining democratic party. This study used the approach mixed method (qualitative and quantitative) with descriptive methods. These results indicate that Implementation of e-voting methods as a medium of political participation in SMAN 1 Manonjaya the class president election researcher can conclude goes well, look at the level of political participation of the students in choosing higher than the selection by using the conventional method. Based on the data using statistical calculations, researchers can conclude that there is a fairly strong correlation between the methods of e-voting as a means of political participation to civic responsibility.